IDENTIFIKASI BIJIH BESI WALENRANG KABUPATEN LUWU DENGAN METODE GEOMAGNET - Aryadi Nurfalaq; Rahma Hi. Manrulu; Novi Pardi (Universitas Cokroaminoto Palopo, 2020)
Walenrang area which has the potential for iron ore mineralization. This study aims to create a subsurface model of iron ore in Santandung Village, Walenrang area based on geomanget data. The method used is geomagnetic by identifying differences in the susceptibility of subsurface rocks. Field data acquisition is done by creating a grid. The residual magnetic anomaly map obtained is then filtered for continuation upwards of 20 m and reduction to the poles for easy interpretation. The results of the eduction to the poles obtained a magnetic value of -450 - 700 nT. The subsurface rocks of Santandung Village have a susceptibility value of 0.029 - 0.3144 SI in an area of 0.2 ha at a depth of 0 - 32 m which is identified as basalt. The iron ore formed in Santandung Village is the result of basalt mineralization.